2001
DOI: 10.1063/1.1389474
|View full text |Cite
|
Sign up to set email alerts
|

Are lithium hydride clusters purely ionic? Study using model potentials and density-functional theory

Abstract: Articles you may be interested inStructure, stability, and dissociation of small ionic silicon oxide clusters [SiOn +(n = 3, 4)]: Insight from density functional and topological exploration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Analysis of the vibrational frequencies by Chen et al shows that with T d symmetry Li 4 H 4 has tetracentered bonding and is more rigid when compared to the tricentered bonded structure with D 4 h symmetry. The optimized geometry of Li 5 H 3 is a distorted cube with F-center vacancy and also has a tail of a Li atom attached to it; the same has been reported by Koutecky et al The optimized geometry of Li 5 H 4 is a distorted cube with a tail of a Li atom; a similar structure is found for its cationic counterpart, in contradiction to the structure reported by Bertolus et al For Li 5 H 5 we find a chair-type structure, and Li 6 H 4 has a caplike structure, in agreement with Koutecky et al…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Analysis of the vibrational frequencies by Chen et al shows that with T d symmetry Li 4 H 4 has tetracentered bonding and is more rigid when compared to the tricentered bonded structure with D 4 h symmetry. The optimized geometry of Li 5 H 3 is a distorted cube with F-center vacancy and also has a tail of a Li atom attached to it; the same has been reported by Koutecky et al The optimized geometry of Li 5 H 4 is a distorted cube with a tail of a Li atom; a similar structure is found for its cationic counterpart, in contradiction to the structure reported by Bertolus et al For Li 5 H 5 we find a chair-type structure, and Li 6 H 4 has a caplike structure, in agreement with Koutecky et al…”
Section: Resultssupporting
confidence: 87%
“…The exchange correlation functional, B3LYP, is a widely used hybrid functional comprised of Becke’s three-parameter exchange functional and the Lee–Yang–Parr correlation functional . It has been shown that B3LYP yields good results on structures and energetics of ion-covalent clusters and has been successfully employed to investigate the ground state geometries and electronic structure calculations of the Li n H m cluster. ,,, Hadipour et al have employed the B3LYP functional with 6-311G++(2d, 2p) basis set to predict geometries, binding energies, atomic charges,Li nuclear magnetic shielding, and EFG tensors of small Li n H m ( m ≤ n ≤ 4) clusters. The present work employs the B3LYP functional with 6-311G++(d, p) basis set; the double plus version in the basis set adds the diffuse function to the hydrogen and Li atom; and the p function is added for the H atom and d function for the Li atom.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations